Endoscopic assisted orchiectomy in Herman’s tortoises (Testudo hermanni sp.) - Paries, S.; Funcke, S.; Ziegler, L.; Lierz, M.; Wüst, E. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: Male tortoises in captivity are often aggressive against other males or females, in particular during mating season related to hormonal influences (testosterone). Castration in males is the treatment of choice in many vertebrate species. A novel technique of minimal invasive castration is presented for Herman’s tortoises (Testudo hermanni).Material and methods: The procedure was performed in ten mature males. An endoscope (2.7 mm/30° angled) was inserted into a prefemoral incision on each side. The testicle was resected after ligation of the gubernaculum testis and the spermatic cord using hemoclips.Results: Each testicle could be removed in approximately 20 minutes. Complications like hemorrhage or damage of adjacent tissue did not occur and all animals recovered uneventfully.Conclusions and clinical relevance: Using the bilateral prefemoral entrance offers an alternative option for orchiectomy in Herman’s tortoises without dissection of the shell. Thus complications like hemorrhage or impaired wound healing followed by sequestration of the bone flap are prevented. Because of the anatomical settings and the risk of tissue damage and time consumption, a unilateral approach is not recommended. Fasting the animals is necessary due to the voluminous gastrointestinal tract of this herbivorous tortoise and emptying the urinary bladder provides more space for manipulations in the coelomic cavity and prevents clipping and cutting of adjacent organs. The magnification via the endoscope is beneficial for orientation in the coelomic cavity, which is formed by the extremely convex carapace. Without this equipment it is challenging to visualize the dorsocaudally located gonads through the relatively small incision and the inserted instruments might block the view at the surgical field. Administration of hemoclips achieved a good hemostasis and the testicles could be resected without major blood loss. The described technique is a gentle method for resection of the testicles in this species and can be adapted to other European tortoise species of equal size.
Keywords: Castration; bilateral; surgery; reptile